Catheter ablation vs. thoracoscopic surgical ablation in long-standing persistent atrial fibrillation: CASA-AF randomized controlled trial. (29th August 2020) - Haldar, Shouvik; Khan, Habib Rehman; Boyalla, Vennela; Kralj-Hans, Ines; Jones, Simon; Lord, Joanne; Onyimadu, Oluchukwu; Satishkumar, Anitha; Bahrami, Toufan; De Souza, Anthony; Clague, Jonathan R; Francis, Darrel P; et al.
Abstract: Aims : Long-standing persistent atrial fibrillation (LSPAF) is challenging to treat with suboptimal catheter ablation (CA) outcomes. Thoracoscopic surgical ablation (SA) has shown promising efficacy in atrial fibrillation (AF). This multicentre randomized controlled trial tested whether SA was superior to CA as the first interventional strategy in de novo LSPAF. Methods and results : We randomized 120 LSPAF patients to SA or CA. All patients underwent predetermined lesion sets and implantable loop recorder insertion. Primary outcome was single procedure freedom from AF/atrial tachycardia (AT) ≥30 s without anti-arrhythmic drugs at 12 months. Secondary outcomes included clinical success (≥75% reduction in AF/AT burden); procedure-related serious adverse events; changes in patients' symptoms and quality-of-life scores; and cost-effectiveness. At 12 months, freedom from AF/AT was recorded in 26% (14/54) of patients in SA vs. 28% (17/60) in the CA group [OR 1.128, 95% CI (0.46–2.83), P  =   0.83]. Reduction in AF/AT burden ≥75% was recorded in 67% (36/54) vs. 77% (46/60) [OR 1.13, 95% CI (0.67–4.08), P  =   0.3] in SA and CA groups, respectively. Procedure-related serious adverse events within 30 days of intervention were reported in 15% (8/55) of patients in SA vs. 10% (6/60) in CA, P  =   0.46. One death was reported after SA. Improvements in AF symptoms were greater following CA. Over 12 months, SA was more expensive and provided fewer quality-adjusted life-years (QALYs) compared with CA (0.78 vs. 0.85, P  =   0.02). Conclusion : Single procedure thoracoscopic SA is not superior to CA in treating LSPAF. Catheter ablation provided greater improvements in symptoms and accrued significantly more QALYs during follow-up than SA. Clinical Trial Registration: ISRCTN18250790 and ClinicalTrials.gov: NCT02755688 Graphical Abstract: